2020
DOI: 10.3390/ijerph17207435
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Conditions and Whole Salivary IL-17A and -23 Levels among Young Adult Cannabis sativa (Marijuana)-Smokers, Heavy Cigarette-Smokers and Non-Smokers

Abstract: In the United States, prevalence of marijuana-use has doubled in the past 2 decades. The aim was to compare the periodontal conditions and whole-salivary IL-17A and IL-23 levels among young adult marijuana-smokers, heavy cigarette-smokers and non-smokers. Self-reported marijuana-smokers, heavy-cigarette-smokers, non-smokers with periodontitis and periodontally-healthy non-smokers were included. Demographic data was recorded and full-mouth plaque index (PI), bleeding on probing (BoP), probing depth (PD) and cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…A major limitation of the present study is that the results were entirely based on in-vitro evaluation of aqueous extracts from both herbs. Several clinical studies have shown that habits such as tobacco smoking and systemic diseases including poorlycontrolled diabetes mellitus are risk factors of periodontitis and dental caries [31][32][33][34][35][36][37][38]. Such risk-factors are known to compromise outcomes of oral therapeutic interventions [39]; and promotion of microbial colonization in the supra-and subgingival oral biofilm [40,41].…”
Section: Saussurea Costusmentioning
confidence: 99%
“…A major limitation of the present study is that the results were entirely based on in-vitro evaluation of aqueous extracts from both herbs. Several clinical studies have shown that habits such as tobacco smoking and systemic diseases including poorlycontrolled diabetes mellitus are risk factors of periodontitis and dental caries [31][32][33][34][35][36][37][38]. Such risk-factors are known to compromise outcomes of oral therapeutic interventions [39]; and promotion of microbial colonization in the supra-and subgingival oral biofilm [40,41].…”
Section: Saussurea Costusmentioning
confidence: 99%
“…In a recent study, although small in sample size, marijuana and heavy cigarette smokers exhibited comparable clinicoradiographic periodontal status, although salivary IL-17A and IL-23 concentrations were higher in the cannabis-using group (Javed et al 2020). There is a need for further research in this area to better ascertain and define the clinical characteristics of marijuana-associated periodontal disease.…”
Section: Knowledge Gaps and Cluesmentioning
confidence: 92%
“…The combined epidemiologic evidence from a growing number of primary studies and related review articles associates marijuana consumption with negative periodontal health consequences (Jamieson et al 2010; Duane 2014; Zeng et al 2014; Meier et al 2016; Shariff et al 2017; Ortiz et al 2018; Atuegwu et al 2019; Chisini et al 2019; Mofidi et al 2019; Javed et al 2020; Keboa et al 2020; Yazdanian et al 2020; Mayol et al 2021). A clinical example of periodontitis in a cannabis smoker is presented in Figure 2.…”
Section: Marijuana Use and Periodontal Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well-known that levels of destructive inflammatory cytokines such as interleukin 1-beta and tumour necrosis factor-alpha are higher in the unstimulated whole saliva (UWS), gingival crevicular fluid (GCF) and peri-implant sulcular fluid (PISF) of patients with periodontitis and peri-implantitis. [36][37][38][39][40] In addition, periodontitis and peri-implantitis are also associated with an increased colonization of pathogenic microbes such as bacteria viruses and yeasts in the oral biofilm (OB). [41][42][43][44] It is therefore hypothesized that is that the number of patients that had attained graduate-level education were higher in the control compared with the test group.…”
Section: Ta B L E 5 Mean ± Standard Deviation Of Periodontal Clinicor...mentioning
confidence: 99%